Parenting Stress Levels Among Working Mothers in ROC Operational Unit: Tingkat Stres Parenting di Kalangan Ibu Bekerja di Unit Operasional ROC - Yulinda Ardi Setyaningtyas; Lely Ika Mariyati (Psikologia : Jurnal Psikologi, 2025)
General Background Parenting stress commonly emerges when parents face continuous emotional and caregiving demands. Specific Background Working mothers often experience dual responsibilities between professional duties and childcare, creating additional psychological pressure within organizational settings. Knowledge Gap Empirical descriptions of parenting stress across varied child ages in specific workplace environments remain limited, particularly in operational units with intensive computer-based tasks. Aims This study aims to describe parenting stress levels among working mothers employed at the PT TIF-3 ROC Unit. Results Using a descriptive quantitative design with purposive sampling of 53 mothers and a reliable parenting stress scale, findings show that 81% of participants fall within moderate to high stress categories, with parental distress identified as the dominant aspect compared to difficult child and parent–child dysfunctional interaction dimensions. Novelty The study provides a contextualized profile of parenting stress within a telecommunications operational center, integrating workplace demands with caregiving challenges. Implications The findings highlight the need for family-friendly workplace policies, social support systems, and stress management programs to assist working mothers in balancing professional and parenting roles. Keywords: Parenting Stress, Working Mothers, Dual Roles, Parental Distress, Workplace Psychology Key Findings Highlights Majority of participants reported moderate–high caregiving strain Emotional burden scored highest among measured dimensions Organizational context linked with time pressure and limited support